Feasibility of Teaching Module in Curriculum Merdeka Integrated Green Chemistry to Improve Science Process Skills and Student Learning Independence - Fitri, Zelisa Nudia; Burhanuddin, Burhanuddin; Sani A, Yunita Arian (Journal of Science and Science Education, 2024)
The implementation of the Curriculum Merdeka was already implemented in 2022. Teaching modules are one of the new terms in the implementation of the Curriculum Merdeka (IKM). Teaching module is another name for lesson plans (RPP) in the 2013 Curriculum, but it is more complex and can be used as teaching materials that can be modified by teachers. Science learning, especially chemistry, requires students to understand science facts and concepts in daily life. Therefore, it is necessary to develop teaching modules that can make learning more contextual. An approach that can be integrated into developing teaching modules is the green chemistry approach. Chemistry learning, which is generally abstract, can be linked to the environment so that learning can be more contextual. The development of teaching modules that contain learning steps and integrate the principles of green chemistry in the form of experimental activities is expected to increase students' learning independence and science process skills. This research is a type of development research that refers to the steps of the ADDIE model. The feasibility of the teaching module developed was analyzed using a Likert scale and a percentage of agreement (PA) formula. Based on calculations, the average validity value of the teaching module was 3.9, with very valid category. Meanwhile, the percentage of agreement obtained 79%, which means the teaching module is reliable. Based on these conclusions, the teaching module developed is feasible to use because it is included in the valid and reliable category